Understanding Consumer Acceptability and Sensory Drivers of Liking in Montepulciano Wines from Brazil and Beyond - Tamara Cristina Melz; Rochele Cassanta Rossi; Valmor Ziegler; Amanda Dupas de Matos (Beverages, 2025)
Brazil is an important wine producer in Latin America, with the Santa Catarina (SC) region gaining prominence for producing high-quality wines. Among new red varieties cultivated in SC, Montepulciano has recently gained attention. Despite the growing interest in Montepulciano wines in Brazil, no studies have investigated Brazilian consumer perceptions of this varietal. This gap underscores the need for research to better understand acceptance for this emerging varietal in Brazil. This study aimed (i) to advance consumer insights of Montepulciano wines by evaluating the acceptability of Montepulciano wines from Brazil and those from other countries, and (ii) to identify the key attributes influencing acceptance. Participants (n = 103) evaluated six national and international wines for overall liking and sensory characteristics using the check-all-that-apply technique. The drivers of liking for aroma were floral and red/dark berries, whereas leather and alcohol penalized liking. In-mouth, sweetness, red/dark berries, and soft tannins drove liking, whereas astringent, sour, and bitter impacted liking negatively. Among the Brazilian wines, differences were perceived to be more pronounced for aroma than flavor and mouthfeel. The findings highlight the market potential of Brazilian Montepulciano wines, with liking comparable to some Italian and Chilean counterparts. Understanding consumer sensory responses to these wines is crucial to support production strategies that align with market demands.